L’efficacité de la politique budgétaire en économie ouverte - Sheikh, Munir; Grady, Patrick; Lapointe, Paul (L'Actualité économique)

(untitled) (HEC Montréal, 1980)
AbstractThe debate between keynesians and monetarists on the effectiveness of fiscal policy has been going for quite a long time, and all efforts to resolve it have met with little success. While everyone would agree that the controversy can only be resolved on empirical grounds, there is no agreement among the two schools as to what constitutes an appropriate test of their respective theories. In this paper, a small macroeconomic model has been developed which incorporates the major elements of the keynesian-monetarist debate and which can produce either keynesian or monetarist results, depending upon the values taken by the particular sets of coefficients. The model has not been estimated and is not designed, therefore, to evaluate the actual impact of fiscal policy measures in Canada. Rather the coefficients of the model have been either borrowed from existing models or set a priori, in order to identify those aspects or parameters of the model which are most important in determining the effectiveness of fiscal policy. Simulations performed with the model indicate a number of factors that are critical in producing either Keynesian or monetarist results. These are: 1) the expected—real—interest elasticity of private real investment; 2) the substitutability between government bonds, money and other assets; 3) the specification of wage behaviour and the degree of influence of price expectations; 4) the sensitivity of nominal interest rates to changes in the inflationary expectations; 5) the extent to which future taxes are anticipated by consumers and 6) the mechanism for determining the price of exports.